(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2018)
The development of newer and easy to use ICT applications especially those that allow social interactions has led to in-creased user levels and experiences. It amazes to see the young operating a smart phone with no challenges unlike their parents. Although these applications have come of age, it is important to address the moral and ethical issues that have emanated with these new applications. This paper addresses moral and ethical issues related to various applications in ICT. It specifically identities personal morals and ethics as the main agents of inculcating moral and ethical behaviors in the development of and usage of ICT related applications. It discusses the role played by morals and ethical behavior in ICT, Social networking sites and tools, and mobile phone applications (mobile apps). It recognizes the role of application developers and general users of ICT in instilling ethical behaviors among themselves and to other remote users. In conclusion, it identifies the critical roles of all types of users and proposes that all should be guided by their personal morals and ethical values that define their characters.